Egypt : a short history - Tignor, Robert L. (Princeton ; Oxford : Princeton University Press, 2010)
"This is a sweeping, colorful, and concise narrative history of Egypt from the beginning of human settlement in the Nile River valley 5,000 years ago to the present day. Accessible, authoritative, and richly illustrated, this is an ideal introduction and guide to Egypt's long, brilliant, and complex history for general readers, tourists, and anyone else who wants a better understanding of this vibrant and fascinating country, one that has played a central role in world history for millennia︢a︣nd that continues to do so today." "Respected historian Robert Tignor, who has lived in Egypt at different times over the course of five decades, covers all the major eras of the country's ancient, modern, and recent history. A cradle of civilization, ancient Egypt developed a unique and influential culture that featured a centralized monarchy, sophisticated art and technology, and monumental architecture in the form of pyramids and temples. But the great age of the pharaohs is just the beginning of the story and Egypt: A Short History also gives a rich account of the tumultuous history that followed︢f︣rom Greek and Roman conquests, the rise of Christianity, Arab-Muslim triumph, and Egypt's incorporation into powerful Islamic empires to Napoleon's 1798 invasion, the country's absorption into the British Empire, and modern, postcolonial Egypt under Nasser, Sadat, and Mubarak." "This book provides an indispensable key to Egypt in all its layers︢a︣ncient and modern, Greek and Roman, and Christian and Islamic."--BOOK JACKET.
The land and people -- Egypt during the Old Kingdom -- The Middle and New Kingdoms -- Nubians, Greeks, and Romans, circa 1200 BCE-632 CE -- Christian Egypt -- Egypt within Islamic empires, 639-969 -- Fatimids, Ayyubids, and Mamluks, 969-1517 -- Ottoman Egypt, 1517-1798 -- Napoleon Bonaparte, Muhammad Ali, and Ismail : Egypt in the nineteenth century -- The British period, 1882-1952 -- Egypt for the Egyptians, 1952-1981 : Nasser and Sadat -- Mubarak's Egypt -- Conclusion: Egypt through the millennia.
Includes bibliographical references and index.
Keywords: Egypt -- History